Prevalence of diabetes mellitus and prediabetes in the adult Romanian population: PREDATORR study2. (6th May 2015) - Mota, Maria; Popa, Simona Georgiana; Mota, Eugen; Mitrea, Adina; Catrinoiu, Doina; Cheta, Dan Mircea; Guja, Cristian; Hancu, Nicolae; Ionescu‐Tirgoviste, Constantin; Lichiardopol, Radu; Mihai, Bogdan Mircea; Popa, Amorin Remus; et al.
Abstract: Background: The PREDATORR (PREvalence of DiAbeTes mellitus, prediabetes, overweight, Obesity, dyslipidemia, hyperuricemia and chronic kidney disease in Romania) study is the first national study analyzing the prevalence of diabetes mellitus (DM) and prediabetes, and their association with cardiometabolic, sociodemographic, and lifestyle risk factors in the Romanian population aged 20–79 years. Methods: This was an epidemiological study with a stratified, cross‐sectional, cluster random sampling design. Sociodemographic, lifestyle, and anamnestic data were collected through self‐ and interviewer‐administered questionnaires, and biochemical assays and oral glucose tolerance tests were performed. Results: In all, 2728 participants from 101 clinics of general practitioners were randomly selected, with a probability proportional to population size according to the 2002 Romanian Census. The participation rate was 99.6%. Impaired glucose regulation (prediabetes, known and unknown DM) was found in 28.1% of the study population. The overall age‐ and sex‐adjusted prevalence of DM was 11.6% (95%CI 9.6%–13.6%), of which 2.4% (95%CI 1.7%–3.1%) had unknown DM. The prevalence of DM increased with age and was higher in men than in women. The age‐ and sex‐adjusted prevalence of prediabetes was 16.5% (95%CI 14.8%–18.2%), with the highest percentage in the 60–79 year age group and in women. Obesity, abdominal obesity, dyslipidemia, low education level, and a family history of diabetes were associated with glucose metabolism disorders. Conclusions: The PREDATORR study shows a high prevalence of impaired glucose regulation in the adult Romanian population, providing data on the prevalence of DM and prediabetes and their association with several risk factors.